Mecha-Ude. Mechanical arms, 3 - Koyoka, Yoshino (Koyoka, Yoshino. Meka-ude., 2026)
Kita-Kagami City is a pretty normal place ... except that some people have gotten their hands on Mecha-Ude: powerful mechanical life forms that attach themselves to human hosts and have awesome capabilities. When middle-school student Hikaru accidentally activates a mysterious Mecha-Ude named Alma, he forms an unlikely bond with the talking arm. But where did Alma come from? And why are shadowy organizations with dangerous Mecha-Ude of their own suddenly after them, determined to capture Alma at all costs?